Heart failure is the strongest predictor of acute kidney injury in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction - Matějka, Jan; Varvařovský, Ivo; Rozsíval, Vladimír; Herman, Aleš; Bláha, Karel; Večeřa, Jan; Lazarák, Tomáš; Novotný, Vojtěch; Mužáková, Vladimíra; Vojtíšek, Petr (Kardiologia Polska, 2016)
BACKGROUND: ST elevation myocardial infarction (STEMI) patients treated by primary percutaneous coronary intervention (PCI) are at higher risk of acute kidney injury (AKI) than patients undergoing PCI in stable clinical conditions. This fact suggests that mechanisms other than contrast nephrotoxicity are involved. AIM: To evaluate the incidence, risk factors, and consequences of AKI in patients undergoing primary PCI for STEMI in current daily practice. METHODS: Analysis of all consecutive patients who underwent primary PCI over a one-year period. AKI was defined as an increase in serum creatinine ≥ 50% or 26.5 μmol/L (AKIN criteria) from the baseline within 48 h. RESULTS: A total of 202 patients were included. AKI occurred in 25 (12.4%) subjects. Baseline characteristics and in-hospital complications of the patients with and without AKI did not differ significantly except for age (69 ± 13 vs. 62 ± 12; p = 0.003), female gender (48.0% vs. 26.6%; p = 0.035), hypertension (88.0% vs. 62.7%; p = 0.013), left ventricular ejection fraction (40% ± 12% vs. 49% ± 14%; p = 0.002), cardiogenic shock (44.0% vs. 5.1%; p < 0.0001), use of intravenous diuretics (76.0% vs. 26.0%; p < 0.0001), ventricular arrhythmias (24.0% vs. 3.4%; p = 0.001), and in-hospital mortality (24.0% vs. 3.4%; p = 0.001). In multivariate analysis heart failure remained the only independent correlate of AKI. CONCLUSIONS: AKI was an frequent and serious complication of STEMI in patients treated by primary PCI. Heart failure was the strongest predictor of AKI. Other risk factors including contrast medium volume, baseline renal function, diabetes, and age failed to predict AKI.
Keywords: Male; retrospektivní studie; srdeční selhání; Risk Factors; kontrastní látky; Age Factors; Aged; infarkt myokardu s elevacemi ST úseků; mužské pohlaví; senioři; ST Elevation Myocardial Infarction; incidence; senioři nad 80 let; lidé; ženské pohlaví; Contrast Media; Heart Failure; Humans; rizikové faktory; věkové faktory; Aged, 80 and over; Acute Kidney Injury; koronární angioplastika; Retrospective Studies; Female; lidé středního věku; Incidence; Percutaneous Coronary Intervention; akutní poškození ledvin; Middle Aged